(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study was conducted in Bidar district of Karnataka, where 150 eggs were collected from surrounding five different villages. The eggs were hatched with 67% hatchability. Chicks were reared with all standard managemental practices. Twenty healthy female birds of different plumage colour namely brown, black and black with yellow tinge were selected and separated into three different pens before the laying stage (at 16th week). The first lay was observed in the brown plumage colour birds at 20th week of age followed by black and black with yellow tinge-coloured birds. Total number of egg produced, external qualities like egg weight, egg length, egg width and shape index were studied. The total number of eggs produced in brown, black & black with yellow tinge were 468, 411 and 392 eggs, respectively. The study showed that brown coloured birds laid more eggs with significantly higher egg weight than other two coloured birds. Differences in egg length and egg width were statistically significant (P<0.05) in three different plumage birds. The highest shape index was observed in black yellow tinge and was statistically different from the other two plumage colours.